MEMBANGUN KEDEKATAN EMOSIONAL KONSUMEN: PERAN BRAND PERSONALITY DAN EMOTIONAL ATTACHMENT TERHADAP LOYALITAS PELANGGAN PADA KAFE SENANDUNG - Apia Septira, Ika; Desiana, Ika; Ramadhani, Wulan (Jurnal Ekonomi Bisnis Kompetif, 2025)
The rapid growth of the café industry has intensified competition based on customer experience and emotional relationships. This study aims to examine the effects of brand personality and emotional attachment on customer loyalty at Kafe Senandung. Using a quantitative explanatory design, data were collected from 100 respondents and analyzed through multiple linear regression. The results indicate that brand personality (β = 0.547; p < 0.05) and emotional attachment (β = 0.441; p < 0.05) have positive and significant effects on customer loyalty. Simultaneously, both variables significantly influence customer loyalty (F = 43.807; p < 0.05) with a coefficient of determination of R² = 0.475. These findings suggest that customer loyalty in local cafés is more effectively developed through emotional attachment reinforced by a consistent brand personality